MODERN METHODS OF RECOVERY OPERATIONS IN PATIENTS WITH COLOSTOMY. - G.N. Rayimov; D. Rakhimov; A.R. Tillaboldiyev; Sh.Sh. Dexqonov; Sh.Kh. Qosimov (Scholar Express Journals, 2023)
Literature data on the results of reconstructive surgeries performed in patients with a previously applied colostomy were analyzed. The issue of restoring the integrity of the large intestine is quite relevant in colorectal surgery, the imposition of colostomy varies from 7 to 63 %. Despite the improvement of existing and development of new methods of reconstructive operations, the active use of intraoperative and postoperative diagnostic methods, it is not possible to completely avoid complications. The incidence of failure of colonic anastomosis sutures reaches 3.8-14.6%. Further study and development of methods of reconstructive operations after colostomy is needed to minimize the number of postoperative complications and improve the results of treatment of patients with colorectal pathology.
Keywords: Colostomy; reconstructive operations on the intestine